AI education for clinicians - Tim Schubert; Tim Oosterlinck; Robert D. Stevens; Patrick H. Maxwell; Mihaela van der Schaar (EClinicalMedicine)
Summary: Rapid advancements in medical AI necessitate targeted educational initiatives for clinicians to ensure AI tools are safe and used effectively to improve patient outcomes. To support decision-making among stakeholders in medical education, we propose three tiers of medical AI expertise and outline the challenges for medical education at different educational stages. Additionally, we offer recommendations and examples, encouraging stakeholders to adapt and shape curricula for their specific healthcare setting using this framework.